Zastosowanie wybranych modeli zmiennych jakościowych do klasyfikacji kredytobiorców - Chrzanowska, Mariola (Application of Selected Models for the Borrowers' Classification, 2005)
The work presents research on paying off the occasional credits received in March 2004. The sample consists of 162 borrowers. According to the data from the end of July 2004, 82 borrowers pay off the credit regularly and 80 fail to pay off the credit. The aim of the report is to prepare a dichotomic classification of borrowers with the use of the logit and probit models.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 521-528